Силуэты женщин в прозе Людмилы Улицкой в гендерном аспекте - Nowakowska, Jana (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The main female characters in Ludmila Ulitskaya’s stories are mostly “little women” – residents of communal areas and outcasts of society – those who are now called marginal. In general, the writer presents a reflection on the complexity of the spiritual path a woman goes through in search of her individual self and identity in the social and cultural space. Ulitskaya reveals to the readers her profiles of women of the Soviet era who are placed in a pseudoegalitarian gender system, and that is why they fight for identity, feeling that Soviet society is not their native and natural sphere of existence.
Women’s profiles in the prose of Ludmila Ulitskaya from a gender perspective
Sylwetki kobiet w prozie Ludmiły Ulickiej w aspekcie genderowym